SOME RESEARCH MILESTONES WHERE CHEMISTRY AND NUTRITION ARE INEXTRICABLY INTERTWINED - Frans Umbu Datta; Christina Olly Lada (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2022)
Abstract History, as always, helps us reflect on our humble beginnings or maybe our golden era. It is an invaluable learning curve for those who learned anything through reflection before doing anything else. This review is an effort to raeveal briefly some of the research milestones that lead to the progressive development of the science of nutrition with the support of chemistry. The experiment of Lavoisier on carbon dioxide production in the late eighteen century has set the scene. Chemistry and nutrition, together, have accomplished so much and contributed to human lives. Our improved health and the provision of healthy animal products for human consumption are some examples. Chemistry has assisted nutritionists in better comprehending the mechanisms of actions of nutrients in the prevention and therapy of some diseases besides their metabolic roles and maintenance of body functions in animals and humans. The most recent findings demand a better understanding of cascades of structural changes of nutrients during digestion and assimilation. Personalised nutrient recommendations and precision nutrition will be the future of nutrition science, where chemistry remains its backbone.